Empowerment Evaluation (Better Evaluation)
Empowerment Evaluation is an approach which provides communities with the tools and knowledge that allows them to monitor and evaluate their own performance. First developed by David Fetterman who describe it a s “the use of evaluation concepts, techniques, and findings to foster improvement and self-determination.”